Antioxidant properties of aqueous and methanol extract from Tinospora crispa and its ability to Attenuate Hydrogen Peroxide-induced stress injury in human umbilical Vein Endothelial cells. - S.K., Ihsan; H.A., Zulkhairi; Md. Akim, Abdah; J.A. , Daryl; I. , Noramalina; M.A., Rasadah; M., Shahidan; M.S , Zamree; K.A.K. , Kamilah; Azlan, Azrina; N.H, Mohd. Kamal; Mohd Esa, Norhaizan; et al. (Medwell Online, 2011)
The aimed of this study was to investigate the antioxidant properties of T. crispa as well as its ability to attenuate the release of oxidant markers in induced oxidation in Human Umbilical Vein Cells (HUVECs). In vitro studies of antioxidant properties of T. crispa showed the DPPH scavenging activity of T. crispa Aqueous (TCAE) and Methanol Extract (TCME) were 82±1.78 and 73±1.01%, respectively. FRAP value of TCAE and TCME were 1.04±0.27 and 1.64±0.06 mmol L-1, respectively. Total Flavonoids Content (TFC) of TCAE and TCME were 205.58±3.5 and 223±10.49 mg QE g-1 sample, respectively while Total Phenolics Content (TPC) of TCAE and TCME were 32.58±0.68 and 41.64±0.97 mg GAE mg-1 sample, respectively. The antioxidant enzymes activities (CAT, SOD and GPx) in HUVECs treated with T. crispa extracts to counter the oxidative effect by hydrogen peroxide (H2O2) and lipid peroxidation activity by Malondialdehyde (MDA) were also measured. The result showed TCAE and TCME at a concentration ranges from 100-600 μg mL-1 significantly increased (p<0.05, 0.01) the level of CAT, SOD and GPx. Results of MDA assay showed significant reduction (p<0.05, 0.01) of MDA level in HUVECs treated with TCAE and TCME. Taken together, the findings suggest that T. crispa extracts can effectively protect HUVECs against oxidative stress by H2O2 which might be of importance in the treatment of cardiovascular diseases.